ANALISIS MODAL KERJA PENGOLAHAN DAN PERDAGANGAN KOPI ARABIKA BEANS (OSE) KECAMATAN KINTAMANI, BANGLI - I Made Adi Parimartha; I Ketut Satriawan; Wayan Widia (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2022)
Coffee is one of the potential plantation sectors that continues to be developed at the production level and for the industrial and trade sectors. To process coffee to be ready for market, several stages of processing need to be done. The company requires the cost of processing coffee until the coffee is ready to be traded. The costs incurred in processing coffee are called working capital. The objectives of this study are (1) to know the processing of arabica coffee until coffee is ready to be traded both between islands and exports in Bangli Regency, (2) determine the working capital components of Arabica coffee processing until coffee is ready to be traded between islands and exports in Bangli Regency, (3) Formulating working capital for processing Arabica coffee until coffee is ready to be traded both between islands and exports needed by Arabica coffee companies in one delivery period. This study uses fieldwork research methods and library research. The research was conducted in Kintamani Subdistrict because this area is the best Arabica coffee-producing area in Bali with a distinctive taste of coffee with an orange aroma. Based on the research, it was found that the order of the coffee processing consisted of preparation of raw materials, spindle sorting, stripping of fruit skin, fermentation, washing, drying, splitting of horn skin, sorting coffee beans, packaging, and shipping to consumers between islands and exported. The working capital components of Arabica coffee companies in Kintamani District are raw materials, water, labor, shipping, and administrative costs. The working capital of Arabica coffee processing in business units in Kintamani District is Rp. 9,401.92 per kg of raw materials, and there are additional administrative and shipping costs of Rp. 7,000,000 for the process of shipping finished products to Arabica Coffee.